Анализ применения пластинчатого теплообменного оборудования в процессе производства экстракционной фосфорной кислоты - Бабак, Татьяна Геннадиевна; Хавин, Геннадий Львович (Харьковская научно-производственная корпорация "ФЭД", 2008)
The problem of wet phosphoric acid plant modernization is considered. Some positions where plate heat exchangers may be installation are presented. Current status state and perspective view of plate heat exchangers using are discussed.
Keywords: экстракция; пульпа; отвод тепла; гипс; охлаждение